Monitoring of environmental flow outcomes in a large river basin: The Commonwealth Environmental Water Holder's long‐term intervention in the Murray–Darling Basin, Australia. (29th August 2019) - Gawne, Ben; Hale, Jenni; Stewardson, Michael J.; Webb, James A.; Ryder, Darren S.; Brooks, Shane S.; Campbell, Cherie J.; Capon, Samantha J.; Everingham, Penny; Grace, Mike R.; Guarino, Fiorenzo; Stoffels, Rick J.
Abstract: The Murray–Darling Basin in south‐eastern Australia contains over 70, 000 km 2 of wetlands and floodplains, many of which are in poor condition. In response, Australian governments have committed to a major restoration program, the Murray–Darling Basin Plan that includes management of 2, 750 Gl of environmental water to protect and restore aquatic ecosystems. The restoration is being undertaken within an adaptive management framework that includes monitoring the outcomes of environmental flows in seven river valleys. This paper provides an overview of the 5‐year monitoring project and some preliminary results. Monitoring design considered the Basin Plan's environmental objectives, conceptual models of ecosystem responses to flow, and an outcomes framework linking flow responses to the environmental objectives. Monitoring indicators includes ecosystem type, vegetation, river metabolism, and fish. Responses are evaluated to identify the contribution of environmental flows to Basin Plan environmental objectives and continual improvements in management. The program is unique in that it seeks to monitor long‐term outcomes of environmental flows at the river basin scale. Despite many challenges, the monitoring has become a key part of the adaptive management of environmental flows in the Murray–Darling Basin.